Energy dissipation in WC-Co coated A356.2/RHA composites - Siva Prasad Dora; Shoba Chintada; Tualsi Radha Palukuri; Srinivasa Rao Pujari (Engineering Science and Technology, an International Journal, 2020)
Energy dissipation, usually, mechanical damping and storage modulus of WC-Co coated A356.2 and their composites dispersed with silica rich rice husk ash (RHA) particulates have been studied in this work. All the specimens are coated using HVOF technique with an optimum coating thickness of 100 µm as obtained by MATLAB. The damping and storage moduli have been measured using dynamic mechanical analyzer at three distinct frequencies (0.1, 1 and 10 Hz) over a temperature range of 35 °C to 150 °C. Introspection of these results reveals that the mechanical damping and storage modulus has been improved with the incorporation of RHA and further increases with the increase in the RHA content. Furthermore, coated WC-Co samples demonstrate higher mechanical damping than the base alloy and its composites, however, a loss in the storage modulus has been noticed which is due to the presence of W2C phase. Porosity, hardness and the residual stresses are the mechanisms responsible for the increase in mechanical damping of WC-Co coated Al/RHA composites.